Government Finance Statistics Manual 2014 - De Clerck, Sage (Manuals and Guides, 2015)
The 2007-09 international financial crisis underscored the importance of reliable and timely statistics on the general government and public sectors. Government finance statistics are a basis for fiscal analysis and they play a vital role in developing and monitoring sound fiscal programs and in conducting surveillance of economic policies. The Government Finance Statistics Manual 2014 represents a major step forward in clarifying the standards for compiling and presenting fiscal statistics and strengthens the worldwide effort to improve public sector reporting and transparency.